Enhancer of zeste homologue 2 (EZH2) is a reliable immunohistochemical marker to differentiate malignant and benign hepatic tumors - Hajósi-Kalcakosz Szofia; Dezső Katalin; Bugyik Edina; Bödör Csaba; Paku Sándor; Pávai Zoltán; Halász Judit; Schlachter Krisztina; Schaff Zsuzsa; Nagy Péter (BMC, 2012)
Abstract Background The immunohistochemical demonstration of Enhancer of zeste homologue 2 (EZH2) proved to be a useful marker in several tumor types. It has been described to distinguish reliably hepatocellular carcinomas from liver adenomas and other benign hepatocellular lesions. However, no other types of malignant liver tumors were studied so far. Methods To evaluate the diagnostic value of this protein in hepatic tumors we have investigated the presence of EZH2 by immunohistochemistry in hepatocellular carcinomas and other common hepatic tumors. EZH2 expression was examined in 44 hepatocellular carcinomas, 23 cholangiocarcinomas, 31 hepatoblastomas, 16 other childhood tumor types (rhabdomyosarcoma, neuroblastoma, Wilms' tumor and rhabdoid tumor), 17 metastatic liver tumors 24 hepatocellular adenomas, 15 high grade dysplastic nodules, 3 biliary cystadenomas, 3 biliary hamartomas and 3 Caroli's diseases. Results Most of the malignant liver tumors were positive for EZH2, but neither of the adenomas, cirrhotic/dysplastic nodules, reactive and hamartomatous biliary ductules stained positively. Conclusions Our immunostainings confirm that EZH2 is a sensitive marker of hepatocellular carcinoma, but its specificity is very low, since almost all the investigated malignant liver tumors were positive regardless of their histogenesis. Based on these results EZH2 is a sensitive marker of malignancy in hepatic tumors. In routine surgical pathology EZH2 could be most helpful to diagnose cholangiocarcinomas, because as far as we know this is the first marker to distinguish transformed and reactive biliary structures. Although hepatoblastomas also express EZH2, the diagnostic significance of this observation seems to be quite limited whereas, the structurally similar, other blastic childhood tumors are also positive. Virtual Slides The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/1173195902735693